RADIOGRAPHY OF THE MARITIME BORDERS IN AFRICA - LÓPEZ MARTÍN, ANA GEMMA (Journal of the Spanish Institute for Strategic Studies, 2020)
One of the aspects that most affects maritime security is, undoubtedly, the proper establishment of borders between States, to the extent that each has clear extension of its jurisdiction. This is particularly relevant for Spain in the case of Africa, insofar as its waters are the main means of entry into our country. The objective of this study is to explain which African maritime boundaries are definitively fixed - either by agreement or by international judgment-. The analysis of this meaningful delimitation practice is of great importance for understanding both the areas that enjoy stability in the matter and, by exclusion, which are still outstanding. At the same time, raising awareness of the maritime boundaries already in place is an unquestionable stimulus and benchmark for other African States to address their delimitations appropriately.